Vesicular Rash Following Immunisation With BTN162b2 Messenger RNA (mRNA) COVID-19 Vaccine: Vaccine Related or Coincidence? - Mohd Radzniwan A Rashid; Sharifah Najwa Syed Mohamad; Anu Suria; Rokiah Shahra (Cureus Journal of Medical Science, 2024)
The introduction of the COVID-19 vaccines has led to an immense sense of relief for the global population. However, since the introduction of these vaccines, there have been several reports related to the side effects. A young woman presented to her primary care doctor with a vesicular rash three days after the BNT162b2 messenger RNA (mRNA) Pfizer-BioNTech vaccine, which was preceded by a low-grade fever for one day. Our case report highlights the challenges in diagnosing a vesicular rash post the BNT162b2 mRNA vaccine. Identifying the cause of a vesicular rash following vaccination has remained a challenge among primary care practitioners.